Mathematical Modeling of Pediatric Leukemia: Logical Modeling Approach - Lacoste, Valery (2024)
A Master of Science thesis in Mathematics by Valery Lacoste entitled, “Mathematical Modeling of Pediatric Leukemia: Logical Modeling Approach”, submitted in May 2024. Thesis advisor is Dr. Abdul Salam Jarrah. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).